2020
DOI: 10.1097/adm.0000000000000652
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Cannabis Use Among African American Nondaily Smokers

Abstract: Objectives: Cannabis and tobacco dual use is a growing concern in the United States, especially among African Americans (AAs). Dual use increases nicotine dependence and poses negative health effects. Despite decreasing numbers of people who smoke daily, nondaily smokers (NDS) are increasing. Polytobacco use, including blunt use, is higher in AA NDS than AAs who smoke daily. This study examined factors associated with cannabis use among AA NDS. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Almost half of our study sample reported at least one incident of marijuana use, corresponding with rates of marijuana use among cigarette smokers ranging from 27% to 46% in previous studies. 13,15,43,44 Given that many smoking studies use CO as an endpoint for bioverifying tobacco use status, researchers will need to determine how to use this information. Many researchers opt to make marijuana and other drug use exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost half of our study sample reported at least one incident of marijuana use, corresponding with rates of marijuana use among cigarette smokers ranging from 27% to 46% in previous studies. 13,15,43,44 Given that many smoking studies use CO as an endpoint for bioverifying tobacco use status, researchers will need to determine how to use this information. Many researchers opt to make marijuana and other drug use exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…9 Couse of combusted (ie, smoked) marijuana is frequent among cigarette smokers and shares similar health concerns from combustion such as exposure to CO, tar, and many harmful compounds also found in tobacco smoke. [10][11][12] Marijuana use among smokers ranges from 18% to 40% [13][14][15][16] varying by study, population, and survey questions used. Combustion of plant-based material exposes marijuana and tobacco users alike to CO, which impedes oxygen delivery in the body by competing with oxygen for binding to hemoglobin.…”
Section: Introductionmentioning
confidence: 99%